PERENCANAAN SLIPWAY PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA - M. Riza Falahudin; Ady Satria; Slamet Hargono; Priyo Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Slipway which is going to be built is in Fishing Port of Nizam Zachman Jakarta (PPSNZJ). The objective of this final project is to design slipway structure that is able to provide repaired and maintenance service, as well as constructing new ships with 271,71 GT is the maximum weight. From the calculation result, it was obtained that the total length of slipway structure is 152 m, 40 m on the land and 112 m on the sea. The width of this slipway is 13 m. Elements of the structure planned consisted of dimension of longitudinal beams, transverse beams, and plates. Software SAP2000 was used for modeling and analytical calculation of slipway structure. The structure consisted of reinforced concrete with the concrete quality of 30 Mpa. The dimension for the longitudinal beams is 40x25 cm and for the transverse beams is 35x25 cm. The thickness slab of land section is 160 mm, and 60 mm for the concrete cover. The foundations used is spun pile with the depth of 42 m.